Self-Determination And Territorial Integrity Revisited: Reflecting Chagos Advisory Opinion And Its Comparison With West Papua - Fadilah, Irfan; Adirespati, Parusa Seno (Indonesian Journal of International Law, 2019)
The right to self-determination and territorial integrity are amongst the cardinal principles of international law mostly utilised in determining the territory of a state. Both principles are equally protected and guaranteed under international law, and any attempt for total or partial disruption of a territory violates the right to self-determination of peoples. The relation between the two principles is evident in Chagos Advisory Opinion issued by ICJ which states that a former colonial territory detached by a colonial power violates the right to self-determination unless such detachment is based on freely expressed will of the people of the concerned territory. The Chagos Archipelago was originally detached from Mauritius by the UK prior to its independence in 1968. A similar situation was also apparent in Western Papua, in which the Dutch administration attempted to detach it from Indonesia prior to the transfer of sovereignty in 1949 under the name of Dutch Western New Guinea. This attempted detachment became one of the biggest arguments used in supporting Papuan independence since it was narrated that the territories were under a different administration. This article argues that such detachment is considered a disruption of territorial unity, which ultimately violates the right to self-determination of people. Furthermore, it also argues on how Indonesia has sovereignty over Western Papua. Those issues will also be discussed through the lens of international politics, especially in terms of the existence of state interests, both related to the former colonial countries and the international community in addressing the two cases.